Investments and Their Financing Risks and Risk Management Trends in the Last 10 Years - Juhász, Zita; Hollósy, Zsolt; Márton, Jenifer (International Journal of Engineering and Management Sciences, 2020)
The purpose of our literature review was to understand the state of research related to management of risk of corporation’s investments and their finance within the past 10 years. Nowadays the risk management and problem solving are characterized by holistic approach and complexity - and these tendencies we can see clearly. We need to examine the likvidity, financing and investment questions together, because of the interactions between them. They can influenced the corporate value together. The role of risk management in the investments is the  cash-flow smoothing (we mean: cash-flow generated by investment). The field of corporate finance is noticeably inseparable from other areas of business science (at least in the empirical analyses), and even technical issues, like risk management, have long been considered suitable appropriate in an integrated form. The financial and operational hedging has become indispensable elements of the managerial toolbar. The consequence of crisis (from 2007) promotes the birth of many studies that justify it. The researchers are paying close attention the transaction costs, such as costs of contracts or agent costs, and the losses due to information assimetry. The statements of behavioral finance connection with managerial decisions mean important additives in this field.